Facing the Plague: Economic and Political Inequality - Winner, Langdon (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2014)
Hopes for the future of democracy must now confront a basic power shift that has emerged since the early 1970s and is now reaching its advanced stages.   This shift in control over key decisions and policies is clearly visible in my own country, the U.S.A., but is evident in many other nations as well.  At stake is a seemingly ineluctable transfer of power from national governments to the transnational firms; from elected officials to directors of large banks, hedge funds, and global firms; from citizens to plutocrats; from democracy to corporatocracy.
Keywords: Anthropology; economics; politics; sociology.